Design and construction of low-volume concrete road: experiences from China. Issue 2 (17th February 2020) - Wei, Ya; Liang, Siming; Gao, Xiang; Feng, Jiliang
Abstract : Low-volume roads in rural areas constitute the majority of China's road network. Such roads have important social and economic functions; however, the budget available for their construction and maintenance is insufficient. Therefore, there is a need to explore design and construction methods for durable and low-cost low-volume roads. In this study, the experiences of design, construction, and performance evaluation of a low-volume road (LVR) constructed in a mountainous area in southwest China are introduced. A small-sized slab with size of 2.0 m × 2.0 m or less that bears wheel load instead of axle load is found appropriate for application to low-volume roads. The thickness of the small-sized slab ranges from 10 cm to 20 cm, which is related to the slab size. This type of slab broadens the application of concrete pavements to low-cost and durable low-volume roads. It is expected that the results of this study will serve as a demonstration for the design and construction of low-volume roads.